2016
DOI: 10.2146/ajhp150277
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of FDA drug recalls: A 30-month analysis

Abstract: An investigation of FDA drug recalls revealed that the five most common recall reasons were contamination, mislabeling, adverse reaction, defective product, and incorrect potency. Compounding firms were associated more frequently with contamination than were noncompounding firms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 4 publications
2
38
0
8
Order By: Relevance
“…There were few publications about drug recalled in different countries and categories, such as the retrospective analysis by Freeman et al [10] that results in a total of 21,120 products which were recalled during the 30-month study period and recalls of cosmetic and personal care products from 2002 to 2016 [10]. Almuzaini et al [26] demonstrate a total of 653 defective medicines in Canada during their study from 2005 to 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were few publications about drug recalled in different countries and categories, such as the retrospective analysis by Freeman et al [10] that results in a total of 21,120 products which were recalled during the 30-month study period and recalls of cosmetic and personal care products from 2002 to 2016 [10]. Almuzaini et al [26] demonstrate a total of 653 defective medicines in Canada during their study from 2005 to 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hall et al carried out a retrospective study evaluating the relationship between recall companies and medicines recalled by FDA from June 20, 2012, to December 31, 2014. They found that the most common reasons for drug recall were contamination (50.1%) [10]. Also, Almuzaini et al evaluated drug alerts in the UK (2001-2011), they found that contaminations are the most common reasons for drug recall (27%) [25].…”
Section: Discussionmentioning
confidence: 99%
“…The most common reason for product recalls is manufacturing issues. An investigation of FDA drug recalls lists contamination, mislabeling, adverse reaction, defective product, and incorrect potency as common causes for recalls [28]. Other causes include regulatory issues, discontinuation of products from the market, procurement issues, business decisions and natural disasters [7].…”
Section: Discussionmentioning
confidence: 99%
“…the lack of retesting incoming bulk ingredients), batch consistency, shelf-life, and microbial contamination [ 49 , 50 ]. According to a retrospective analysis of all FDA-issued recalls for drugs and biological products issued from 20 June 2012 to 31 December 2014, compounding was associated more frequently with contamination than licensed drugs [ 51 ]. In both France and the UK, compounded CsA formulations are available in glass multi-dose bottles of 10 mL.…”
Section: Discussionmentioning
confidence: 99%